DNA Damage and Activation of cGAS/STING Pathway Induce Tumor Microenvironment Remodeling - Shen, Rong; Liu, Disheng; Wang, Xiaoning; Guo, Zhao; Sun, Haonan; Song, Yanfeng; Wang, Degui (Frontiers in Cell and Developmental Biology, 2022)
DNA damage occurs throughout the tumorigenesis and development. The immunogenicity of DNA makes it to be an immune stimulatory molecule to initiate strong inflammatory responses. The cGAS/STING pathway has been investigated as a critical receptor in both exogenous and endogenous DNA sensing to activate the innate immune response. Growing evidences have indicated that activation of cGAS/STING pathway is critical in antitumor immunity. Recent studies have demonstrated the outstanding promotion of this pathway in tumor combined immunotherapy, accordingly, increased studies focus on exploration of STING pathway agonists and analogues. However, current studies propose the potential promotion of cGAS/STING pathway in tumor initiation and metastasis. Here, we review the molecular mechanisms and activation of cGAS/STING pathway, the relationship between DNA damage and this pathway, particularly highlighting the remodeling of immune contexture in tumor environment (TME) triggered by cascade inflammatory signals. The detailed understanding on TME reprogramming initiated by this pathway may pave a way for development new therapeutic strategies and rational clinical application.